The light well as element of luminous control inside the architectural spaces, case of study: Batlló House - Coral Hinojosa, Sebastián (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
This work took as a case study a specific light well. The Casa Batlló, work of the architect Antoni Gaudí, was subjected to a light simulation, where the percentages of daylight of each floor were obtained from the areas that are adjacent to the light well. Additionally, four case studies were modeled for their respective analysis in which the different percentages obtained in the simulation are compared and the different variables of each case are analyzed. Although the Casa Batlló handles the use of color on the surfaces surrounding the patio, the variable of modifying the size of the windows is also used. With this Gaudí tried to compensate for the power of daylight that exists on the floors superiors, unifying the concept of window size and color treatment on surfaces. The main objective of this work is to know what influence more for the entrance of natural light, if the use of highly reflective colors on the surfaces of the courtyards or to vary the size of the windows. The conclusion is that color influences more effectively the entry of natural light with a 1.4% difference in FLD with the window size variable.